The new geopolitics of terror: demons and dragons - Hopkinson, William (Routledge Focus, 2017)
Introduction -- Lessons from a troubled history -- The Middle East today -- The global reach of Islamism -- The new great game -- The scale of the challenge -- The challenge of strategy -- The new geopolitics of terror -- Demons and dragons